Flypaper Effect and Fiscal Illusion in Village Financial Management: A Case Study of KP Village - Oktarini Khamilah Siregar; Rahima Br Purba; Tri Dessy Ratna Sari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the phenomenon of fiscal illusion and the flypaper effect in the financial management of KP Village in Serdang Bedagai Regency. The research aims to analyze the impact of fiscal decentralization, financial dependency, village income growth, spending efficiency, and the effectiveness of local revenue (PADesa) on village expenditure. Using a quantitative associative approach and multiple linear regression analysis, this study examines financial data from 2015 to 2024. The results show that while village revenue and expenditure have steadily increased, local revenue generation remains low, highlighting the village’s dependence on intergovernmental transfers. The findings confirm the presence of the flypaper effect, where increased transfer funds lead to higher village spending without a corresponding increase in locally generated income. Significant factors influencing village expenditure include land and building tax, degree of decentralization, and spending efficiency, while other variables such as village income growth and transfer income have a limited impact. This study underscores the need for strengthening fiscal independence by enhancing local revenue generation strategies, improving budget management efficiency, and reducing reliance on external transfers. The research contributes to understanding fiscal behavior at the village level and provides policy recommendations to improve financial independence and sustainable village development.